Prevalence of Sodalis glossinidius and different trypanosome species in Glossina palpalis palpalis caught in the Fontem sleeping sickness focus of the southern Cameroon - Kanté Tagueu Sartrien; Farikou Oumarou; Njiokou Flobert; Simo Gustave (Parasite, 2018)
Tsetse flies are the cyclical vector of human and animal African trypanosomiasis. To improve vector control in order to achieve the elimination of human African trypanosomiasis (HAT) and boost the control of animal diseases, investigations have been undertaken on the tripartite association between tsetse, trypanosome, and symbionts. It is in this light that Sodalis glossinidius and different trypanosomes were identified in Glossina palpalis palpalis caught in Fontem in southern Cameroon. For this study, DNA was extracted from whole flies, and S. glossinidius and different trypanosome species were identified by polymerase chain reaction (PCR). Statistical analyses were performed to compare the trypanosome and S. glossinidius infection rates and to look for an association between these microorganisms. Of the 274 G. p. palpalis caught, 3.3% (9/274) were teneral. About 35% (96/274) of these flies harbored S. glossinidius. Of the 265 non-teneral flies, 37.7% were infected by trypanosomes. The infection rates of Trypanosoma congolense “forest type” and Trypanosoma vivax were 26.04% and 18.11%, respectively. About 6.41% of tsetse harbored mixed infections of T. congolense and T. vivax. Of the 69 tsetse with T. congolense infections, 33.33% (23/69) harbored S. glossinidius while 71.86% (69/96) of flies harboring S. glossinidius were not infected by trypanosomes. No association was observed between S. glossinidius and trypanosome infections. Some wild tsetse harbor S. glossinidius and trypanosomes, while others have no infection or are infected by only one of these microorganisms. We conclude that the presence of S. glossinidius does not favor trypanosome infections in G. p. palpalis of the Fontem focus.